HOW DO LIBRARIANS SERVE USERS IN DIGITAL LITERACY ERA? - Eti Sumiati; I Wayan Wijanaraga (Indonesian Journal of Librarianship, 2020)
Problem Statement: Growth and development of science and information technology in the current digital era, also influence the world of literacy towards digital literacy. Librarians as one of the drivers of literacy are demanded to be fast adaptive to the development of digital literacy. The distribution of librarians in the campus of the Institute of Domestic Government is uneven and some libraries do not have librarians. In line with the statement by Supriyanto (2012) that the librarian profession is not as popular as other professional staff, library staff and librarians in particular have all the limitations of both quantity and quality. Purpose: The purpose of this research is to find out the attitudes and strategies that librarians can take in facing challenges in the era of digital literacy. Method: The method used in this research is descriptive method with a qualitative approach Result: The ability of librarians to use technology is considered to be lacking in providing information for librarians and the discovery of uneven distribution of librarians in the campus area of the Institute of Domestic Government and several campuses not having librarians is considered to be able to hamper library development in the era of digital literacy. Conclusion: In dealing with users of various characteristics in the era of digital literacy, librarians are required to have basic abilities, namely: tool literacy; resource literacy; social-structural; research literacy; publishing literacy; emerging technology literacy; and critical literacy. The realization of the role of librarians in the era of digital literacy also requires academic and government support in the use of online libraries, the provision of technology, equitable distribution of human resources, librarian development capabilities and guidance from the government to build a much better library.